Breast imaging reporting and data system (BI RADS): Why don't we use it correctly in the region? - Prvulović-Bunović Nataša; Mastilović Milica; Stankov Maja; Nikolin Borislava (Archive of Oncology)
Breast Imaging Reporting and Data System (BI RADS) is used for the standardization of radiological reports in breast imaging, created by the American college of radiology (ACR). Standardized reports allow breast lesion characterization, malignancy risk assessment, and facilitate communication between doctors. The system is made for everyday clinical practice with the aim of improving the quality of diagnostics and anticipate the comparisons of results with colleagues from other health institutions, while in Serbia to assist in communication with colleagues from the region. The BI RADS system is composed of lexicon recommendations for structured radiological reporting and further management. Most health institutions in Serbia and surrounding countries use it, but in everyday clinical practice the system is not correctly implemented in all institutions. During daily imaging procedures we see radiological reports coming from different institutions in the region. Some of them clearly show that the system is misunderstood and not implemented correctly. Our aim is to evaluate the use of the BI RADS system in everyday clinical practice in Serbia and the region, to explain why it is not used correctly, and to point out the most common mistakes with the desire to make the system work adequately.